الأنماط القيادية في الادارة - ارفيس, مريم (جامعة الوادي - University of Eloued, 2021)
هدف البحث إلى التطرق إلى ماهية الأنماط القيادية في الادارة، فقسم إلى ثلاثة محاور أساسية بداية بماهية القيادة ثم النمط القيادي ثم النماذج المفسرة للنمط القيادي، حيث خلص البحث إلى أنه يوجد الكثير من الأنماط القيادية منها ما هو مثبط للمؤسسة ومنها ما هو مساهم في تطوريها، و الأنماط الحديثة الإيجابية كثيرة و متنوعة وعلى القائد التغيير فيها من وقت لآخر واختيار الأنسب منها حسب الموقف وطبيعة التابعين. The research aims to address the nature of leadership styles in management, It was divided into three main axes, beginning with what the leadership is, then the leadership style, then the explanations of the leadership style, Where the research concluded that there are many leadership styles Some of which are disincentive to the institution, and some that contribute to its development, And positive modern patterns are many and varied The leader must change it from time to time And choose the most appropriate ones according to the situation and the nature of the dependents.
مقال
Keywords: قيادة؛ نمط قيادي؛ مداخل نظرية للنمط القيادي؛ نماذج مفسرة للنمط القيادي; Leadership; Leadership style; Theoretical approaches to leadership style; Explanatory models for leadership style